Hukum Menjamak Salat bagi Tim Penyelamat Perspektif Kaidah Al-Masyaqqah Tajlibu Al-Taisīr: The Ruling on Combining Prayers for Rescue Teams from the Perspective of the Legal Maxim Al-Masyaqqah Tajlibu al-Taisīr (AL-FIKRAH: Jurnal Kajian Islam, 2025)
Jamak prayer refers to the practice of combining two obligatory prayers within one designated time under specific conditions. In disaster response situations, rescue teams may perform jamak prayers due to several influencing factors. This study aims to: first, identify the forms of hardship and obstacles faced by rescue personnel in the field; and second, analyze the application of the legal ruling on jamak prayer for rescue teams within the framework of the Islamic legal maxim al-Mashaqqah Tajlibu al-Taysīr (Hardship Begets Ease). This research adopts a qualitative approach with library research as the primary method. The findings reveal that various factors influence the decision to perform jamak prayers, such as the severity and urgency of the disaster situation, the pressing nature and continuity of rescue operations, limitations of time and space to perform prayers, the physical and psychological condition of the personnel, guidance from religious scholars or spiritual advisors, and reference to the jurisprudential positions of specific Islamic schools of thought. In circumstances where performing prayers at their designated times could hinder life-saving efforts or pose potential danger, jamak prayer becomes a highly relevant and permissible option. This practice aligns closely with the legal maxim al-Mashaqqah Tajlibu al-Taysīr, which provides ease in the face of genuine hardship during emergency conditions. The practical implication of this study is to offer clarity and understanding for rescue teams in disaster response regarding the permissibility of jamak prayer, and to serve as a reference for future scholarly research on this topic.